2018
DOI: 10.1038/s41467-018-07216-8
|View full text |Cite
|
Sign up to set email alerts
|

A common genetic mechanism underlies morphological diversity in fruits and other plant organs

Abstract: Shapes of edible plant organs vary dramatically among and within crop plants. To explain and ultimately employ this variation towards crop improvement, we determined the genetic, molecular and cellular bases of fruit shape diversity in tomato. Through positional cloning, protein interaction studies, and genome editing, we report that OVATE Family Proteins and TONNEAU1 Recruiting Motif proteins regulate cell division patterns in ovary development to alter final fruit shape. The physical interactions between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
234
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(241 citation statements)
references
References 39 publications
5
234
0
2
Order By: Relevance
“…Consistent with this conclusion is the finding that, in rice, a mutation in an α‐tubulin gene ( Srs5 mutant) affected grain dimension traits (Segami et al ., ). Similarly, the interaction between the OVATE family proteins and TRM were shown to regulate cell division and alter fruit shape in tomato (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this conclusion is the finding that, in rice, a mutation in an α‐tubulin gene ( Srs5 mutant) affected grain dimension traits (Segami et al ., ). Similarly, the interaction between the OVATE family proteins and TRM were shown to regulate cell division and alter fruit shape in tomato (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Developmental pathways that affect morphological diversity of plant organs through the interaction with TRM appear to be common in plants. For example, it was shown that the interaction of the OVATE family proteins with TRM regulates cell division and alters fruit shape in tomato, and possibly in melon and cucumber (Wu et al ., ). The high level of cross‐species conservation of pathways controlling grain morphology and weight (Li et al ., ) suggests that the homologs of TRM in wheat might also be involved in biological pathways defining similar traits.…”
Section: Introductionmentioning
confidence: 97%
“…One remarkable example is a 31-kb deletion upstream of tomato OVATE Family Protein 20 (SlOFP20). The deletion is associated with reduced expression of SlOFP20 and contributes to natural fruit shape variation in the tomato germplasm 41 . A 3-bp deletion in the promoter of tomato Al-ACTIVATED MALATE TRANSPORTER9 (Sl-ALMT9) was selected during tomato domestication.…”
Section: Deletions and Inversionsmentioning
confidence: 99%
“…6f). Previous study showed the mutation of STYLISH1(STY1) and NGATHA(NGA), both participate in the development of gynoecium by activating the expression of YUC, resulted in fruit with long and narrow styles in Arabidopsis [22][23]. To better understand of the CsOFP11 gene function, we detected the expression level of AtSTY1, AtNGA, and AtYUC4.…”
Section: Overexpression Csofp11 In Arabidopsismentioning
confidence: 99%